Using lake sediment records to reconstruct bark beetle disturbances in western North America - Jesse Lee Morris (Frontiers of Biogeography)
The recent outbreak of native bark beetles in western North America is unprecedented in severity and scale, at least during the historical period. The aim of this work is to develop a proxy-based methodology to understand how bark beetle disturbances are recorded in lake sediments. Three hypotheses are tested to determine how the ecological impacts of severe spruce beetle (Dendroctonus rufipennis) disturbances are recorded following mortality of Engelmann spruce (Picea engelmannii). Outbreaks are hypothesized to: (1) decrease the ratio of spruce to fir pollen; (2) increase soil erosion and mobilize terrestrial C; and (3) leach foliar N, enhancing algal productivity. To test these hypotheses, sediment cores from spruce beetle-affected basins were analyzed for pollen, insect remains, organic and minerogenic content, and isotopic and elemental concentrations. The dataset was tested statistically using generalized linear mixed models (GLMMs) to determine if the response variables differed significantly between outbreak and non-outbreak periods.